THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY ON CONSUMER SATISFACTION AT PT. DELAMIBRANDS KHARISMA BUSANA - Maduma Sari Sagala; Rifqah Harahap (SEAN Institute, 2022)
The purpose of this study was to determine the effect of product quality and service quality on consumer satisfaction at PT. Delamibrands Kharisma Busana. The population in this research is the consumers of PT. Delamibrands Kharisma Busana which numbered 127 respondents while the technique of determining by accidental sampling with the Slovin formula approach with an error rate of 10%. So that the sample in this study amounted to 56 respondents. The data sources in this study are from primary data and secondary data. Where is the primary data from observations, interviews and questionnaires. While secondary data can be from data that has been documented. While the data analysis technique used is multiple linear regression analysis. The results of the regression analysis are Y = 4,926+ 0,228X1 + 0,296X2 + e which shows that product quality and service quality have a positive and significant effect on customer satisfaction. Whereas the results of the test (t) or partial test show that the product quality has a positive and significant effect on customer satisfaction where it can be seen the value of t arithmetic 3.140> t table 2.006 and the variable service quality also has a positive and significant effect on customer satisfaction where it can be seen the t value of 3,969 > t table 2,006. The results of the coefficient of determination with a correlation regression value of 0.851 means that together the quality of the product and the quality of service to customer satisfaction PT. Delamibrands Kharisma Busana has contributed to a close and positive level. Where the value (R2) of 0.713 (71,3%). So it can be said that 72.4% of the dependent variable variations namely product quality and service quality in the model can explain the variable customer satisfaction at PT. Delamibrands Kharisma Busana while the remaining 28,7% is influenced by other variables outside the model. The other variables that affect consumer satisfaction are the promotional mix, brand image and so on.